ANALISIS KALKULUS PREDIKAT PADA TERJEMAHAN SURAH AL-SAFFAT - Siti Ainim Liusti (Sunan Kalijaga State Islamic University Yogyakarta, 2013)
This study based on Chomsky’s generative grammar that about surface and deep structure. It is supported by Bierwish theory about projection rules, and limits choice theory by Katz and Bierwish. Predicate calculus is a study of sentence structure by relation to the componential meaning of the lexicon. Predicate calculus rests on the deep structure to form a sentence. Deep structure is able to describe such as subject, predicate, object, and others. Verb as a predicate is a core of sentence. The purposes of this research is to formulate the types of verbs and describing it based on predicate calculus. The object of this research is some sentences of the letter translation al-Sa>ffa>t from the Holy Qur’an. There are four types of verbs are : (1) V + NP, it is commonly like V kopula + NP as variation of verb. (2) V + NP + PP, the variation of verb can be V kopula+ NP + PP. (3) V + PP, or verbs can be V kopula + PP. (4) V, without other arguments followed. It can be VP just as a verb. In addition, it is common that the PP may consist of (a) Adj + Prep, and (b) Prep + NP.",